Retina-specific loss of Ikbkap/Elp1 causes mitochondrial dysfunction that leads to selective retinal ganglion cell degeneration in a mouse model of familial dysautonomia - Yumi Ueki; Veronika Shchepetkina; Frances Lefcort (The Company of Biologists, 2018)
Familial dysautonomia (FD) is an autosomal recessive disorder marked by developmental and progressive neuropathies. It is caused by an intronic point-mutation in the IKBKAP/ELP1 gene, which encodes the inhibitor of κB kinase complex-associated protein (IKAP, also called ELP1), a component of the elongator complex. Owing to variation in tissue-specific splicing, the mutation primarily affects the nervous system. One of the most debilitating hallmarks of FD that affects patients' quality of life is progressive blindness. To determine the pathophysiological mechanisms that are triggered by the absence of IKAP in the retina, we generated retina-specific Ikbkap conditional knockout (CKO) mice using Pax6-Cre, which abolished Ikbkap expression in all cell types of the retina. Although sensory and autonomic neuropathies in FD are known to be developmental in origin, the loss of IKAP in the retina did not affect its development, demonstrating that IKAP is not required for retinal development. The loss of IKAP caused progressive degeneration of retinal ganglion cells (RGCs) by 1 month of age. Mitochondrial membrane integrity was breached in RGCs, and later in other retinal neurons. In Ikbkap CKO retinas, mitochondria were depolarized, and complex I function and ATP were significantly reduced. Although mitochondrial impairment was detected in all Ikbkap-deficient retinal neurons, RGCs were the only cell type to degenerate; the survival of other retinal neurons was unaffected. This retina-specific FD model is a useful in vivo model for testing potential therapeutics for mitigating blindness in FD. Moreover, our data indicate that RGCs and mitochondria are promising targets.